(untitled) (Research, Society and Development, 2019)
The present article aims to describe the similarities and differences present in the literature on the subject concerning the concept of difficulties and learning disorders. Also discussed in this study were factors that influence learning difficulties and disorders, reflecting on their possible causes. The research carried out is of the bibliographic type, with a qualitative character. Data collection was carried out in the second half of 2018, in the following electronic databases: Scielo, Google Academica, Bireme, in the repositories of dissertations and theses of universities. The studies indicate that the difficulties and learning disorders present similar symptomatology, but the differentiated etiology being that the difficulties are related to the extrinsic factors and the disorders to factors intrinsic to the student. Therefore, it is important to emphasize the importance of teachers of different levels of education to know such approaches so that their pedagogical interventions reach a more effective and meaningful learning within the.